2022
DOI: 10.1177/00986283211058069
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Concrete Examples Enhances the Learning of Abstract Concepts: A Replication Study

Abstract: Background Prior research suggests that the teaching of abstract concepts can be enhanced by the use of concrete examples, but there are few controlled studies. Objective To replicate key findings from experiment one from Rawson et al. (2015). Method Experiment participants studied definitions of abstract concepts from psychology, either with or without concrete examples. The replication differed from Rawson et al. by using a paid online participant pool, of non-psychology students, and a trimmed methodology f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…Teachers also suggested that the user experience of the toolkit could be further enhanced by using examples from life. Micallef and Newton (2022) showed that using concrete examples greatly improves the learning of abstract concepts. Abstract concepts are concepts which do not possess physical forms or references ( Harpaintner et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers also suggested that the user experience of the toolkit could be further enhanced by using examples from life. Micallef and Newton (2022) showed that using concrete examples greatly improves the learning of abstract concepts. Abstract concepts are concepts which do not possess physical forms or references ( Harpaintner et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bunun yerine kavram öğretim yöntem ve tekniklerinden yararlanılabilir. Bunlara ek olarak somut yaşantıya dayalı, öğrenci merkezli öğretim yöntem ve tekniklerine de çokça yer vermek gerekir (Micallef & Newton, 2022).…”
Section: Introductionunclassified